Exploring the Socioeconomic Dynamics and Technological Adaptation among Farmers: Implications for Sustainable Agricultural Development and Rural Livelihoods in Jaipur, India - , Meenakshi Jakhar; , R. N. Sharma; , B.S. Badhala; , Jhabar Mal Tetarwal (Archives of Current Research International, 2024)
The research was conducted in Jaipur district of Rajasthan. There are 23 AAO departments under the jurisdiction of Deputy Commissioner of Agriculture, Jothwara (Jaipur). Among these, 4 AAO departments viz. Hingonia, Jobner, Boraj and Bichun were deliberately chosen for this study because the AAO circle is next to SKNAU, Jobner is within a radius of 20 km, researchers from the school respectively many people are making technological improvements in nearby villages and farmers are also active. A total of 120 participants were selected from these four AAO circles. Judging from the entire health history of farmers benefiting from Nongtang, the majority of farmers benefiting from Nongtang are middle-aged (35 to 51 years old) (58.33%). Primary school graduates (20.00%), farmers are union members (37.50%), their share of average annual income (77.50%) is Rs. 1,26,781 to Rs. 4,72,303 and farmers share small land. category (38.33%). Moreover, most of the beneficiary farmers (44.17%) have moderate farming experience ranging from 15 to 31 years, (23.19%) farmers use PM Kisan application, (70.00%) farmers use information technology, (68%) 34) consider agriculture as the main business. job. The relationship between income and technological change shows that there is a positive relationship between education level, social participation, annual income, insured land, agriculture, agricultural practice and knowledge. The beneficiary's social profile indicates education, community involvement, annual income, land ownership, farm practice use, and data-effective and relevant job creation and annual income. The correlation between the profile of the beneficiaries and their social variables shows a positive relationship between the level of education, social participation, and annual income. There is a significant relationship between the use of agricultural practices and the change in personal property and the education level of family members. Agricultural knowledge and information are important and positively related to changes in household members' education levels and ownership of agricultural equipment.